The role of hypoxia regulated microRNAs in cancer. - McCormick, R; Buffa, F; Ragoussis, J; Harris, A (2010)
The molecular response of cancer cells to hypoxia is the focus of intense research. In the last decade, research into microRNAs (miRNAs), small RNAs which have a role in regulation of mRNA and translation, has grown exponentially. miR-210 has emerged as the predominant miRNA regulated by hypoxia. Elucidation of its targets points to a variety of roles for this, and other hypoxia-regulated miRNAs (HRMs), in tumour growth and survival. miR-210 expression correlates with poor survival in cancer patients, and shows promise for future use as a tumour marker or therapeutic agent. The role of miR-210 and other HRMs in cancer biology is the subject of this review.